Management of Students Potential Development Using the Data Mining Clustering Method in MAN 2 Malang City - Romlah, Siti (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Every human being is endowed with potential in himself. This potential must be managed correctly to produce academic and non-academic achievements. An achievement is a form of proving the success of learning and mastery of science. Many madrasas have an achievement crisis due to the mismanagement of students’ potential. This study aims to provide new formulations to map students’ potential and develop the potential for achievement. They are taking the pilot of Madrasah Aliyah Negeri (MAN) 2 Malang City as an Islamic educational institution. This research method is field-based with a descriptive qualitative approach, where data is taken from the principal, vice principal for student affairs, and the head of Ma'had there. The results showed that, first, the potential management developed was to trace students’ potential through the acceptance of academic and non-academic achievement pathways according to the vision and character of the madrasah. The next stage is the development of potential: 1) cleaning and integration. Potential finalization results are filtered through unstructured interview test methods and excellent program-based question presentations. This stage produces clusters of science, language, and Islam; 2) pattern recognition. Merit awards evidence clustering based on the school's flagship program; 3) knowledge presentation. In the form of periodic evaluations to ensure that students have been able to achieve achievements. Second, the pattern of potential development is based on Islamic boarding schools, and each cluster has a markaz supported by a laboratory.